2021
DOI: 10.1021/acsnano.1c05164
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Encoded Bioluminescent System for Fast and Highly Sensitive Detection of Antibodies with a Bright Green Fluorescent Protein

Abstract: A method for fast and highly sensitive detection of antibodies in serum would greatly facilitate the early diagnosis of disease and infection and dose optimization of therapeutic antibody. Bioluminescence detection with LUMABS (renamed mNeonG-LUMABS, where mNeonG is short for mNeonGreen) sensors based on bioluminescence resonance energy transfer (BRET) between blue-emitting luciferase Nluc and green fluorescent protein (FP) mNeonGreen has been demonstrated to enable fast detection of antibodies directly in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Tuning the relative affinities of the competing DarkBiT and SmBiT components yielded an optimized sensor for anti-HIV1-p17 with a 48 ± 8-fold increase in luminescent intensity. This dynamic range is 10-fold better than the previously reported sensor based on NanoBiT (NB-LUMABS) and 6-fold better than the most optimized BRET-based LUMABS sensor (Clover4-LUMABS-HIV) . This comparison is not completely fair, as the latter represent ratiometric sensor systems, whereas dark-LUMABS-HIV #3 by itself is an intensiometric sensor.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Tuning the relative affinities of the competing DarkBiT and SmBiT components yielded an optimized sensor for anti-HIV1-p17 with a 48 ± 8-fold increase in luminescent intensity. This dynamic range is 10-fold better than the previously reported sensor based on NanoBiT (NB-LUMABS) and 6-fold better than the most optimized BRET-based LUMABS sensor (Clover4-LUMABS-HIV) . This comparison is not completely fair, as the latter represent ratiometric sensor systems, whereas dark-LUMABS-HIV #3 by itself is an intensiometric sensor.…”
Section: Resultsmentioning
confidence: 66%
“…This dynamic range is 10-fold better than the previously reported sensor based on NanoBiT (NB-LUMABS) and 6-fold better than the most optimized BRET-based LUMABS sensor (Clover4-LUMABS-HIV). 26 This comparison is not completely fair, as the latter represent ratiometric sensor systems, whereas dark-LUMABS-HIV #3 by itself is an intensiometric sensor. However, we recently showed that intensiometric assays can be rendered ratiometric by the addition of green enhanced Nanolantern (GeNL), a tight fusion protein between NanoLuc and mNeongreen.…”
Section: Resultsmentioning
confidence: 99%
“…16 Numerous kinds of fluorescent probes (e.g., fluorescent proteins, fluorescent dyes and fluorescent nanomaterial-based probes) have been employed to label and trace different molecules, proteins, cells, and tissues and their dynamic progress. [49][50][51][52][53][54][55][56][57][58] In particular, fluorescent proteins are suitable for labeling various cells, viruses, genes and so forth; fluorescent dyes are appropriate for imaging and analyzing antibodies, peptides, small molecule drugs and so on. With significant advances in nanotechnology, nanomaterials (e.g., II-VI quantum dots (QDs), carbon dots (CDs), upconverting nanoparticles (UCNPs) and silicon-based nanoparticles (SiNPs)) featuring attractive optical properties, have been exploited as novel high-performance fluorescent nanoprobes for biomedical imaging applications.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…, fluorescent proteins, fluorescent dyes and fluorescent nanomaterial-based probes) have been employed to label and trace different molecules, proteins, cells, and tissues and their dynamic progress. 49–58 In particular, fluorescent proteins are suitable for labeling various cells, viruses, genes and so forth; fluorescent dyes are appropriate for imaging and analyzing antibodies, peptides, small molecule drugs and so on. With significant advances in nanotechnology, nanomaterials ( e.g.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…The ratiometric signal can remain constant, regardless of the decay of the bioluminescence intensity, which makes the detection result more accurate. Proximity-based BRET probes have been proved to be powerful tools for monitoring protein–protein interactions, protein–ligand interactions, and molecular proximity. However, current BRET-based probes mainly employs specific proteins or peptides as recognition moiety, which allows the detection of only a limited number of targets. The recognition of the probes mainly relies on intermolecular interactions, which is difficult to transform the binding of targets into a change in BRET signal .…”
Section: Introductionmentioning
confidence: 99%